2007
DOI: 10.1111/j.1600-0714.2007.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the neoplastic nature and biological potential of sporadic and nevoid basal cell carcinoma syndrome‐associated keratocystic odontogenic tumor

Abstract: The results implied that heparanase expression may be correlated with the neoplastic properties of KCOT, particularly in NBCCS-associated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…These major EMPs have been shown to have preferential expression in dental tissues, in particular the developing enamel producing ameloblasts (24). Prior studies have determined the localization of apoptosis and proliferation markers and an invasion-associated enzyme heparanase (25,26). Although these markers were broadly expressed, relative expression levels were useful in the potential classification of NBCCS from sporadic KCOTs and nonspecified odontogenic cysts.…”
Section: Discussionmentioning
confidence: 99%
“…These major EMPs have been shown to have preferential expression in dental tissues, in particular the developing enamel producing ameloblasts (24). Prior studies have determined the localization of apoptosis and proliferation markers and an invasion-associated enzyme heparanase (25,26). Although these markers were broadly expressed, relative expression levels were useful in the potential classification of NBCCS from sporadic KCOTs and nonspecified odontogenic cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Favoring the neoplastic nature of OK, various studies showed the expression of bcl-2, p53, p63, and Ki-67 14,15 . OKs have show loss of heterozygosity for PTCH, which is also indicative of its neoplastic nature, explaining the close relationship with the NBCCS 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently reclassified as keratocystic odontogenic tumor, the OK is a benign, aggressive cystic lesion of the jaws 14 . Favoring the neoplastic nature of OK, various studies showed the expression of bcl-2, p53, p63, and Ki-67 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…It is locally destructive, despite its bland histological features. 13,14 Agram et al 15 examined (10) odontogenic keratocysts for loss of heterozygosity of tumor suppressor genes. The loss of heterozygosity was seen in 7 of 10 cases, the mutation of genomic DNA in these cysts supports the hypothesis that they are neoplastic rather than developmental in origin.…”
Section: Introductionmentioning
confidence: 99%